The role of angiogenesis and its inhibitors in gynecology: From physiological embryonic development to tumorigenesis and metastasis Rolle der Angiogenese und ihrer Inhibitoren in der Gynäkologie: Von der Embryonalentwicklung bis zur Tumorgenese und Metastasierung - Alkatout, I.; Maass, N.; Jonat, W.; Mundhenke, C.; Schem, C. (Gynäkologe, 2013)
Angiogenesis describes the neoformation of blood vessels which develop by budding and sprouting of the existing vessel system. Solid tumor growth is dependent on the surrounding growing capillary network providing the tumor with essential nutrients and oxygen. The pathophysiological role of angiogenesis could be shown for multiple benign (endometriosis, menorrhagia, leiomyomatosis, ovarian hyperstimulation syndrome, preeclampsia and placental hypoperfusion syndrome) and malignant (especially metastasized and therapy-refractory breast cancer, ovarian cancer, cancer of the fallopian tube and the primary peritoneal cancer) diseases. Diseases that are very much dependent on (neo) angiogenesis can be treated with various anti-angiogenic agents. Due to the broad spectrum of side effects of established angiogenesis inhibitors which are mostly given in combination with chemotherapeutic agents, this therapeutic approach is mostly limited to malignant diseases, such as breast cancer, ovarian cancer, cancer of the fallopian tube and primary peritoneal carcinoma. This review provides an overview of the current state of knowledge in the anti-angiogenic therapy of gynecological diseases and will give a perspective of potential future implications of new therapeutic agents. © 2012 Springer-Verlag Berlin Heidelberg.
CRIS-Team Scopus Importer:2022-11-17
Keywords: Angiogenesis inhibitors; Growth factors; Metastasis; Neovascularization; Tumorgenesis